Islamic Education Planning Management in a Review of Fakhru Razi's Tafsir - Sa'adah, Aulia Nurus; Citraningsih, Diningrum (Program Magister Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2024)
Islamic education in the world today is experiencing a period of intellectual stagnation, among the signs that renewal is absent, and if anything, it is losing fast with advances in the technological, social, and political fields. Lack of future planning in education management thus making management less structured. Implementing Islamic education planning management in accordance with the Qur'an is expected to have a positive impact. The goal is to form a generation that has a good understanding and practice of religion. This approach is considered a necessity to make education structured, so that it can help a person to be more devoted to Allah SWT and apply moral principles in everyday life. Thus, the implementation of Islamic education planning management is expected to contribute significantly in shaping individuals who have noble character and live life in accordance with the teachings of Islam. The purpose of the researcher linking the management of Islamic Education planning in the review of Fakhru Razi's interpretation is to understand and apply Islamic principles in Education planning through the interpretation of the verses of the Qur'an, so that education can be organized in accordance with Islamic values and teachings. Fakhruddin Ar-Razi emphasizes the importance of combining Islamic religious principles with a management approach in managing the education system, as well as its implementation in planning Islamic education holistically. Thus, the aim of this study is to that researchers choose the type of literature study research through a qualitative approach using an analytical descriptive approach that is normative in nature that is adjusted to the source of literature sources. The results of his research are 1) Management constitutes social a systematic science for understanding why and how people work together.2) There are lafadz that are commensurate with planning, one of which is the practice in surah Al-Kahfi verse 48 which means hope.3) Some verses related to Islamic Education planning management. Islamic education planning management is an effort made systematically and organized to achieve high quality education in accordance with the study of the Qur'an and Hadith, as interpreted by Fakhru Razi in the Qur'an surah Al-Imran verses 35 and 39, Al-Hasyr verse 18, Al-Hujurat verse 13.